Cyanobacteria as a Promising Alternative for Sustainable Environment: Synthesis of Biofuel and Biodegradable Plastics - Agarwal, Preeti; Soni, Renu; Kaur, Pritam; Madan, Akanksha; Mishra, Reema; Pandey, Jayati; Singh, Shreya; Singh, Garvita (Frontiers in Microbiology, 2022)
Abstract With the aim to alleviate the increasing plastic burden and carbon footprint on Earth, the role of certain microbes that are capable of capturing and sequestering excess carbon dioxide (CO2) generated by various anthropogenic means was studied. Cyanobacteria, the photosynthetic prokaryotes, are a promising alternative for carbon sequestration as well as biofuel and bioplastic production because of their minimal growth requirements, higher efficiency of photosynthesis and growth rates, presence of considerable amounts of lipids in the thylakoid membranes and cosmopolitan nature. These microbes could prove beneficial to future generations in achieving sustainable environmental goals. Their role in the production of polyhydroxyalkanoates (PHAs) as a source of intracellular energy and carbon sink is being utilized for bioplastic production. PHAs have emerged as well-suited alternatives for conventional plastics and a parallel competitor to petrochemical-based plastics. Although a lot of studies have been done where plants and crops are being used as sources of energy and bioplastics, however, cyanobacteria have been reported to have a more efficient photosynthetic process strongly responsible for increased production with limited land input along with an acceptable cost. The biodiesel production from cyanobacteria is an unconventional choice for a sustainable future as it curtails the toxic sulphur release, and checks the addition of aromatic hydrocarbons having efficient oxygen content, with promising combustion potential, thus making them a better choice. Here, we aim at reporting the application of cyanobacteria for biofuel production and their competent biotechnological potential, along with achievements and constraints in its pathway towards commercial benefits. This review paper also highlights the role of various cyanobacterial species that are a source of green and clean energy along with their high potential in the production of biodegradable plastics. Keywords: biodegradable, bioplastics, biofuel, biopolymer, carbon sequestration, clean energy, cyanobacteria, polyhydroxyalkanoates, sustainable.